(untitled) (Research, Society and Development, 2021)
Piper amalago L. is a medicinal plant traditionally used as a healing agent for wounds, burns, abscesses, boils, and insect bites. The current study aimed to evaluate the possible effects of the aqueous crude extract obtained from P. amalago leaves, in different concentrations and in different incubation times, using the in vitro model of mouse fibroblasts (3T3). The extract was tested in different concentrations at the 24 h incubation time for analysis of cell viability, cytotoxicity, proliferation, cell morphology, immunostaining, adhesion and cell spreading assays, as well as to determine the hydroxyproline concentration and activity of the metalloproteinase MMP2. Morphologically, after exposure to the concentrations of 15 and 150 µg/mL, the cells maintained the morphology, yet a greater number of cells with more expansions of the cell body and larger than the control cells were observed. The treated cell culture also showed a greater number of cells, larger cells, a greater expansion of the cell body, adherent cells spread over the substrate, and a more juxtaposed, central and spherical nucleus. The treatment induced greater cell adhesion to the polymer, fibronectin, and collagen I. Biochemical results showed a significant increase in the hydroxyproline amino acid after exposure for 96 h. The extract did not induce loss of cell viability until the concentration reached 150 µg/mL, positively modulating proliferation, morphology, adhesion, degree of spreading, and organization of microfilaments. The extract also promoted a significant increase in the hydroxyproline amino acid.